miR-19b-3p promotes human pancreatic cancer Capan-2 cells proliferation by targeting phosphatase and tension homolog - Song, Meiyi; Sun, Mengxue; Xia, Lu; Chen, Wei; Yang, Changqing (Annals of Translational Medicine; Vol 7, No 11 (June 14, 2019): Annals of Translational Medicine (Focus on: “Application of Artificial Intelligence to Radiology”), 2019)
Background: Pancreatic cancer is a common cancer with a poor prognosis and an increasing morbidity. miR-19b-3p has been implicated in some cancers, however, its role in pancreatic cancer is unclear. Methods: Human pancreatic cancer cell line Capan-2 cells were transfected with miR-19b-3p mimic and inhibitor. Cell proliferation was measured by 5-Ethynyl-2'-deoxyuridine (EdU) staining assays. Cell cycle of Capan-2 cells was examined by flow cytometry. The expression of phosphatase and tension homolog (PTEN) was determined by real-time quantitative polymerase chain reaction (PCR) and western blotting analysis. Functional rescue experiments were performed through PTEN overexpression and miR-19b-3p mimic by using EdU staining assays. Results: miR-19b-3p mimic significantly increased miR-19b-3p while miR-19b-3p inhibitor decreased that. EdU staining showed that miR-19b-3p overexpression promoted Capan-2 cells proliferation while miR-19b-3p inhibition decreased that. Flow cytometry analysis of cell cycle indicated that miR-19b-3p overexpression increased the percentage of Capan-2 cells in S phase while miR-19b-3p inhibition decreased that. PTEN was confirmed to be a target gene of miR-19b-3p and PTEN overexpression eliminated the proproliferation effects of miR-19b-3p in Capan-2 cells. Conclusions: Our study demonstrates that miR-19b-3p promotes Capan-2 cells proliferation by targeting PTEN.